2015
DOI: 10.1016/j.ijso.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Conventional versus fast track anaesthesia in an unselected group of patients undergoing revisional bariatric surgery

Abstract: Introduction:Fast track care has proven to be safe and effective in primary bariatric procedures. The number of more complex revisional procedures is expected to rise over the next years. The aim was to evaluate the potential benefits and safety of a fast-track protocol in an unselected group of patients undergoing Roux-en-Y Gastric Bypass (rRYGBP) as revision. Method: For this retrospective study, all patients undergoing rRYGBP between January 2005 and December 2013 were included and categorized between conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…These programs improve efficiency and reduce postoperative complications, especially after bariatric surgery. Our research group and also others showed that a fast-track approach in the bariatric patient population is safe and efficient [1][2][3][4][5].…”
Section: Introductionsupporting
confidence: 54%
“…These programs improve efficiency and reduce postoperative complications, especially after bariatric surgery. Our research group and also others showed that a fast-track approach in the bariatric patient population is safe and efficient [1][2][3][4][5].…”
Section: Introductionsupporting
confidence: 54%
“…Ó 2016 ðîö³ áóëè îïóáë³êîâàí³ ðåêîìåíäàö³¿ ùîäî ³ìïëåìåí-òàö³¿ êîìïîíåíò³â ERAS â áàð³àòðè÷íó õ³ðóðã³þ [9]. Ïðîòîêîë ïðèñêîðåíîãî âåäåííÿ ï³ñëÿ áà-ð³àòðè÷íèõ âòðó÷àíü (ERABS) áóâ ³ìïëåìåíòîâàíèé â áàãàòüîõ Çàõ³äíîºâðîïåéñüêèõ áàð³àò-ðè÷íèõ öåíòðàõ [5][6][7][8] òà âêëþ÷ຠâ ñåáå êðàùó ïðàêòèêó ïåðåäîïåðàö³éíî¿ ï³äãîòîâêè òà ñòàí-äàðòèçàö³¿ ïåð³îïåðàö³éíî¿ òà ï³ñëÿîïåðàö³éíî¿ äîïîìîãè, ÿêà çàáåçïå÷èòü øâèäêå îäóaeàííÿ ³ ïîë³ïøèòü ðåçóëüòàò ë³êóâàííÿ. Àëå çàëèøàºòüñÿ íåÿñíèì, ÷è âñ³ êîìïîíåíòè êëàñè÷íîãî ïðîòîêîëó (ìàë.…”
Section: âñòóïunclassified
“…Enhanced Recovery After Bariatric Surgery (ERABS) has been implemented in many bariatric centers to optimize the patient pathway care and its safety and efficacy are well known [12][13][14][15]. The ERABS protocol is associated with improved quality of the surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The ERABS protocol is associated with improved quality of the surgical treatment. This includes a best practice of preoperative preparation and standardization of perioperative and postoperative care, which would ensure early recovery and improves the outcome [12][13][14][15]. In 2015, the ERABS protocol was implemented and also morbidly obese patients with ESRD were enrolled in it.…”
Section: Introductionmentioning
confidence: 99%